Pemahaman Ekonomi Islam pada Pengusaha Home Industry Muslim dalam Upaya Penghindaran Riba - Kusumawardani, Media; Yanto, Desri (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Community service activities are undertaken to enhance the understanding of Islamic economics among prospective entrepreneurs in the village of Muara Penimbung Ulu. Comprehension of Islamic economics can encourage entrepreneurs to avoid usury and opt for Islamic banking as an alternative source of business capital. Methodology: The implementation of community service activities took place on August 25, 2023. The activities were conducted in the village of Muara Penimbung Ulu. The stages of community service activities comprised field observations, provision of materials, and participant evaluation. Results: The community service activities proceeded smoothly. The presented material included an understanding of Islamic economics, principles of Islamic economics, prohibited elements in Islamic economics, the differences between Islamic and conventional economics, Sharia contracts in Islamic economics, and Islamic financial institutions. The evaluation results indicated that the participants received the material well. Limitations: The limited Internet access in the village of Muara Penimbung Ulu resulted in participants not being updated on developments in the field of economics. Contribution: Participants experienced improvement in their understanding of Islamic economics. They were able to distinguish between Islamic economics and conventional economics. The participants understood that bank interest constitutes usury (riba) in Islamic economics.